Deaths from international terrorism compared with road crash deaths in OECD countries. Issue 6 (2nd December 2005) - Wilson, N; Thomson, G
Abstract : Objective: To estimate the relative number of deaths in member countries of the Organisation for Economic Co-operation and Development (OECD) from international terrorism and road crashes. Methods: Data on deaths from international terrorism (US State Department database) were collated (1994–2003) and compared to the road injury deaths (year 2000 and 2001 data) from the OECD International Road Transport Accident Database. Results: In the 29 OECD countries for which comparable data were available, the annual average death rate from road injury was approximately 390 times that from international terrorism. The ratio of annual road to international terrorism deaths (averaged over 10 years) was lowest for the United States at 142 times. In 2001, road crash deaths in the US were equal to those from a September 11 attack every 26 days. Conclusions: There is a large difference in the magnitude of these two causes of deaths from injury. Policy makers need to be aware of this when allocating resources to preventing these two avoidable causes of mortality.